Zastosowanie badań eksperymentalnych w nauczaniu jęz yków obcych na prz ykładzie prz yswajania słownictwa - Mac, Agnieszka (Neofilolog, 2010)
The aim of experimental research is to check if an assumed dependency can actually be evidenced in the learning process; to determine the extent to which this can be applied, as well as to determine the quality of the influence of the experimental factor on the outcomes. In other words, did the improvement in fact happen and what increase in effects, or the time taken to achieve them, can be expected. As research problems vary, different research approaches are used. In this paper a classic experimental design with pretest and posttest and a control group will be discussed. This is illustrated using an example of research on vocabulary acquisition. The research discussed compares vocabulary development in the traditional classroom with a multimedia environment.